FRI0071 Outcomes from rheumatology and reproductive health clinic 2013–2016. (12th June 2018) - Murray, K.; Moore, L.; O'Brien, C.; Clohessy, A.; Brophy, C.; Minnock, P.; Mongey, A.B.; Molloy, E.; FitzGerald, O.; Higgins, S.; Higgins, M.; McAuliffe, F.; et al.
Abstract : Background: A multidisciplinary approach to pregnancy in women with rheumatic diseases will ensure best outcomes for mother and baby. 1 Objectives: In 2013, we developed a dedicated nurse-led multidisciplinary Rheumatology Reproductive Health Clinic (RRHC) in order to provide a multidisciplinary service. Methods: 98 women attended the RRHC from January 2013–16. They were prospectively assessed for age, diagnosis, medications, use of assisted reproductive technology (ART) and pregnancy outcomes. Results: The mean (range) age was 35 years. 19–48 The majority of patients had rheumatoid or psoriatic arthritis. The characteristics of the patients is summarised in table 1 and their outcomes in table 2. 24 women were on a biologic DMARD therapy at the time of conception. 10 discontinued in the first semester and 5 in the second trimester. 9 continued throughout their pregnancies. 90% of women surveyed were "very satisfied" with the physical and emotional support received in the clinic. Conclusions: This is the first report of results from a multidisciplinary RRHC. These data show high levels of successful pregnancy outcomes and patient satisfaction. The majority of patients had an inflammatory arthritis. Successful pregnancy outcomes were achieved in 70% of women actively trying to conceive. 38% of patients on biologic DMARDS continued these throughout pregnancy. There were comparable miscarriage rates observed when compared with the general population (14% versus 20%). 2 . Breastfeeding rates were low at 28% compared to the figure of 55% for the general population in Ireland. 3 . Most patients were "very satisfied" with the service. References: [1] Götestam Skorpen C, et al. The EULAR points to consider for use of antirheumatic drugs before pregnancy, and during pregnancy and lactation. Annals of the Rheumatic Diseases2016;75(5):795–810. [2] Weintraub, et al. An initial miscarriage is associated with adverse pregnancy outcomes in the following pregnancy. American Journal of Obstetrics and Gynecology2011;205(3):286.e1-e5. [3] Leahy-Warren P, et al. Normalising breastfeeding within a formula feeding culture: An Irish qualitative study. Women and Birth2017;30(2):e103-e10. Disclosure of Interest: None declared